Postoperative Complications Associated With Metabolic Syndrome Following Adult Spinal Deformity Surgery. Issue 2 (March 2020) - Ye, Ivan B.; Tang, Ray; Schwartz, John T.; Cheung, Zoe B.; Cho, Samuel K.
Abstract : Study Design: A retrospective cohort study. Objective: The objective of this study was to examine the effect of metabolic syndrome on 30-day postoperative complications following corrective surgery for the adult spinal deformity (ASD). Summary of Background Data: Metabolic syndrome has been shown to increase the risk of cardiovascular morbidity and mortality. Few studies have examined the effect of metabolic syndrome on patients with ASD undergoing surgery. Materials and Methods: We performed a retrospective cohort study of patients who underwent spinal fusion for ASD. Patients were divided into 2 groups based on the presence or absence of metabolic syndrome, which was defined as a combination of hypertension, diabetes mellitus, and obesity. Baseline patient characteristics and operative variables were compared between the 2 groups. We also compared the incidence of 30-day postoperative complications between the 2 groups. A multivariable regression analysis was then performed to identify 30-day postoperative complications that were independently associated with metabolic syndrome. Results: A total of 6696 patients were included with 8.3% (n=553) having metabolic syndrome. Patients with metabolic syndrome were more likely to have renal comorbidity ( P =0.042), bleeding disorder ( P =0.011), American Society of Anesthesiology classification ≥3 ( P <0.001), and undergo a long fusion ( P =0.009). Patients with metabolic syndrome had higher rates of 30-day mortality ( P =0.042), superficial surgical site infection ( P =0.006), sepsis ( P =0.003), cardiac complications ( P <0.001), pulmonary complications ( P =0.003), pulmonary embolism ( P =0.050), prolonged hospitalization ( P =0.010), nonhome discharge ( P =0.007), and reoperation ( P =0.003). Metabolic syndrome was an independent risk factor for cardiac complications [odds ratio (OR)=4.2; 95% confidence interval (CI): 1.7–10.2; P =0.001], superficial surgical site infection (OR=2.8; 95% CI: 1.4–5.7; P =0.004), sepsis (OR=2.2, 95% CI: 1.2–3.9; P =0.009), reoperation (OR=1.7; 95% CI: 1.2–2.5; P =0.006), pulmonary complications (OR=1.7; 95% CI: 1.1–2.5; P =0.017), and prolonged hospitalization (OR=1.4; 95% CI: 1.0–1.9; P =0.039). Conclusions: Recognition and awareness of the relationship between metabolic syndrome and postoperative complications following ASD surgery is important for preoperative optimization and perioperative care.